Reform and Exploration of Teaching Modes in Data Processing Courses for Humanities and Social Sciences Majors - Zhang, Liguo; Zhang, Jian; Yu, Kui (International Journal of Social Sciences and Public Administration, 2024)
This article explores innovative teaching methods such as personalized instruction, fostering students' self-learning abilities and creative thinking, integrating multimedia technology for blended learning both online and offline, incorporating research into teaching, diversifying evaluation methods, and enhancing teachers' self-efficacy for improving teaching effectiveness. Taking the course "Python Data Processing and Analysis" as a case study, the article applies these approaches in practical teaching. The research findings indicate a significant improvement in teaching effectiveness, with noticeable enhancements in student engagement and performance.